Novel antioxidative nanotherapeutics in a rat periodontitis model: Reactive oxygen species scavenging by redox injectable gel suppresses alveolar bone resorption. (January 2016) - Saita, Makiko; Kaneko, Junya; Sato, Takenori; Takahashi, Shun-suke; Wada-Takahashi, Satoko; Kawamata, Ryota; Sakurai, Takashi; Lee, Masaichi-Chang-il; Hamada, Nobushiro; Kimoto, Katsuhiko; Nagasaki, Yukio
Abstract: The excessive production of reactive oxygen species (ROS) has been implicated in a variety of disorders, but to date, ROS scavengers have not been widely used for local treatment of inflammation, because they are rapidly eliminated from the inflamed site. We have designed a novel redox injectable gel (RIG) that is formed at 37 °C after disintegration of nano-assembled flower micelles allowing nitroxide radicals to act locally as specific ROS scavengers for the treatment of periodontitis. In the present study, we have confirmed retention of the RIG in the periodontal region, along with its antioxidant-related anti-inflammatory effects, and we have subsequently evaluated the inhibitory effect of the RIG against Porphyromonas gingivalis ( P. gingivalis )-induced alveolar bone loss attributed to ROS. Alveolar bone loss was estimated by morphometry, gingival blood flow was measured using laser Doppler flowmetry, and osteoclast differentiation was evaluated by tartrate-resistant acid phosphatase staining. The results show that the RIG can inhibit P. gingivalis -induced bone loss by antioxidant-related anti-inflammatory actions, and this suggests that the RIG is a promising novel therapeutic agent for the treatment of P. gingivalis -induced periodontitis.